Long-Tailed Macaque (Macaca fascicularis) Population Demographic and Spatial Use Pattern in Telaga Warna, Bogor - Bunga Resa Hartati, Bunga Resa Hartati; Santoso, Nyoto; Arief, Harnios (Jurnal Pengelolaan Sumberdaya Alam dan Lingkungan (Journal of Natural Resources and Environmental Management), 2023)
The Telaga Warna Nature Reserve and Nature Park is one of the animal and fauna conservation and protection areas in West Java, with an area of ​​496.49 ha. The long-tailed monkey is one of the protected animals at Telaga Warna. Based on the IUCN Redlist, long-tailed monkeys are currently included in the endangered species (Endangered). The largest decline in the long-tailed monkey population is due to illegal hunting. Given the declining condition of the long-tailed macaque population, this study was conducted to analyze the demographics of the population and analyze the home ranges of long-tailed macaques in Telaga Warna. The research was conducted in March-May 2021, which was carried out at CA and TWA Telaga Warna. The data collected includes population demographics, home ranges, and habitat use. Analysis of population demographic data used concentration calculations based on sex and age structure, home ranges using a minimum convex polygon and habitat use was analyzed descriptively by comparing conditions between observed groups of long-tailed monkeys. The results of the research on the long-tailed monkey population in the Telaga Warna area consisted of two groups with a total of 64 individuals. The long-tailed macaque population will decrease because it has a regressive population with sufficient space and a low total population density of 0.13 ind/ha. The home range area of ​​group A is 13.8 ha and that of group B is 6.26 ha. The home range area of ​​group B is thought to be influenced by the size and age structure of the group. The long-tailed monkey group both use forest land cover, plantations and water bodies, and are found at an altitude of 1400-1600 masl with gentle to very steep slopes (> 8%).